PELATIHAN PERTOLONGAN PERTAMA KASUS BAROTRAUMA TELINGA PADA NELAYAN DENGAN METODE ROLE PLAY - Nugrahani, Ely Rahmatika; Yulis Anggraeni, Zuhrotul Eka; Imamah Muthoharoh, Nur; Fitriana Lestari, Nurul; Ika Putri, Nanda; Syamsil Arifin, Anisatus; Ramadhani, Rizal; Gabriel F, Dico M. (LPPM Universitas dr. Soebandi, 2023)
ABSTRACT Ear barotrauma was a health threat experienced by fishermen. First aid training for fishermen with barotrauma cases was developed to improve fishermen's ability to provide assistance when barotrauma occurs. This program was developed in line with the Universitas Muhammadiyah Jember Strategic Plan and government policies related to maintaining public health. This program works with fishermen from Watu Ulo Hamlet, Sumberejo Village, Ambulu Jember District. The outcomes result from this program were 1) first aid knowledge and training for fishermen with barotrauma cases, 2) modules or simple books about barotrauma, 3) activity videos, 4) published articles. The methods used to achieve this goal were 1) mentoring, 2) education and 3) practice of first aid training for barotrauma cases. The first aid training program for barotrauma cases was carried out on March 19, 2023 at the Watu Ulo Hamlet Hall, attended by 9 fishermen as regional coordinators. Activities carried out were health screening of the ears, blood pressure, measurement of blood sugar and uric acid levels, as well as training in first aid in cases of barotrauma used the roleplay method. The results of the screening found that 77.7% of fishermen experienced barotrauma, and 100% of fishermen were able to perform first aid for cases of barotrauma. The activity went smoothly and the fishermen were enthusiastic. It is hoped that this activity can continue to develop with full assistance to local fishermen.Keyword: Ear barotrauma, Fishermen, First aid training